2015
DOI: 10.1111/phen.12088
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory responses of Drosophila suzukii females to host plant volatiles

Abstract: Drosophila suzukii Matsumura, an endemic pest in southeast Asia, has invaded Europe and the U.S.A. Unlike most of its closely related sibling species, the serrated ovipositor of D. suzukii permits ovipositing in undamaged fresh fruits. In the present study, volatiles are identified from host plants that are potentially involved in D. suzukii host recognition and oviposition behaviour. It is shown that mated females are attracted to volatiles emitted from intact fruits. The antennally‐active suite of compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 64 publications
6
109
0
Order By: Relevance
“…Thus, these chemicals might help SWD moving through the forest canopy to locate potential host fruits. The detected compounds include volatiles typical for ripening fruits (Abraham et al 2015;Revadi et al 2015), e.g., benzaldehyde and octanal, and others considered common green leaf volatiles. The volatiles may lure the flies to pine trees parasitized by mistletoe.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these chemicals might help SWD moving through the forest canopy to locate potential host fruits. The detected compounds include volatiles typical for ripening fruits (Abraham et al 2015;Revadi et al 2015), e.g., benzaldehyde and octanal, and others considered common green leaf volatiles. The volatiles may lure the flies to pine trees parasitized by mistletoe.…”
Section: Discussionmentioning
confidence: 99%
“…orientation (e.g., Lebreton et al 2012, Faucher et al 2013) and oviposition behaviors (e.g., Stensmyr et al 2012, Linz et al 2013. Revadi et al (2012) showed recently that D. suzukii flies are attracted to odors from intact raspberry, blackberry, blueberry, cherry, and strawberry fruit, indicating that fruit volatiles are important in D. suzukii host location. Similarly, we showed that, when given a choice between fruit extracts and water, female and male D. suzukii are attracted to volatiles from blueberry, cherry, strawberry, and raspberry fruit extracts.…”
Section: Discussionmentioning
confidence: 99%
“…When performing GC-EAD studies, Revadi et al (2012) showed that D. suzukii antennae respond to several compounds emitted from intact raspberry fruit; however, these compounds were not identified. Maistri (2012) identified 16 antennally active compounds to female D. suzukii from blueberries (V. corymbosum 'Duke'): ethyl acetate, butyl acetate, cunene (isopropylbenzene), isocumene (propylbenzene), 1,8-cineole, anhydrolinalool oxide, a-terpinene, tridecane, octanal, tetradecane, trans-caryophyllene, methyl salicylate, hexanoic acid, d-3-carene, geraniol, and a-ionone but their behavioral activity was not tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations